Analisis Rancangan Poros Spindle Mesin Auto Level Buff Menggunakan Perangkat Lunak CAE - Anggi Karmana; Ismet P. Ilyas; Ade Ramdan (Jurnal Teknologi dan Rekayasa Manufaktur, 2022)
The auto level buff machine spindle shaft is a transmission shaft that continues rotation to the buff wheel. This shaft is subjected to a combination of bending and twisting loads, so it is necessary to design analysis regarding the strength of the shaft so that failure does not occur during use. The shaft design analysis will use manual calculations with reference to the failure theory which is then compared with the calculation results based on CAE simulation. The CAE software used are Solidworks Simulation and Ansys Workbench. Based on the results of manual calculations and simulations, there is a difference in Von mises stress, deflection, and safety factors. The results of the design analysis show that the shaft receives an equivalent stress of about 19 MPa and a deflection of about 0.088 mm. The safety factor that occurs is in the range of number 14 which exceeds the minimum safety factor of 1.5. It can be concluded that the spindle shaft design on the auto level buff machine is safe to use.